“ADABIYOT TANITQICH” (“INTRODUCTION TO LITERARY STUDIES”) – A CLASSIC STUDY BY AHMET BAYTURSINOV - Salkynbay, Anar (SCIENCE and SOCIETY, 2026)
This article proposes an evaluation of A. Baytursinuly’s reflections on the concepts of "aytis-tartis" in his work "A Guide to Literature" as a literary term and an anthropological-philosophical idea.